VD_FINDINFO HC / 2012 / 223 vom 21. Februar 2012 - VD Tribunal cantonal (2012)
CONTRAT D'ENTREPRISE, EXPERTISE | 237 al. 2 CPC, 238 CPC, 239 CPC, 320 CPC, 451 ch. 4 CPC, 457 CPC, 465 al. 1 CPC, 471 al. 3 CPC, 405 al. 1 CPC (CH)